Comparative study of dydrogesterone dosage of the duphaston 40mg daily and duphaston 20mg daily in the outcome of pregnancy with threatened miscarriage in husm. - Abd Rahim, Rahimah (2011)
Objective To evaluate the effectiveness and the adverse effect of Duphaston 40mg daily and Duphaston 20mg daily in threatened miscarriage. Methodology This is a prospective randomized controlled trial conducted at Hospital USM, Kubang Kerian Kelantan from 1st of March 2009 until 30th March 2010. A total of 130 patients were studied, 65 patients in Group A for those who is taking Duphaston 20mg daily and the other 65 patients in Group B on Duphaston 40mg daily. Besides the effectiveness, the side effect of the two different dosage of Duphaston is also evaluated. The successful of the pregnancy is measured by continuity of the pregnancy beyond 20weeks of gestation. Result was analysed with Chi-square and Fisher’s Exact test to determine the statistical significant. The test considered significant if p value < 0.05. Results There were higher successful pregnancy in Group B (Duphaston 40mg daily) compared to Group A (Duphaston 20mg daily) (86.7% versus 81.7%). But this is not statistically significant as the p value in multivariate analysis is 0.50 ( p> 0.05). There were no significant differences in adverse effect of the two different dosage of Duphaston. Conclusion Duphaston 40mg daily was not associated with higher chances of successful pregnancy in threatened miscarriage (p = 0.50 in multivariate analysis). There were also no significant differences of adverse effect of the drugs in between the two groups.